Fiscal consequences of the abolition of sugar levies - Cieślukowski, Maciej; Mutascu, Mihai (Economics and Business Review, 2018)
From October 2017 the European Union envisages the abolition of the socalledsugar quotas and minimum prices for buying sugar beet. As a consequence ofthese changes the sugar levies paid by the sugar factories of the Member States willcease to apply. The article identifies the fiscal effects of the abolition of these levies.The European Union and the Member States will lose some of their budget revenues.The structure of Member States’ burdens for GNI payments will also change as wellas their operating balance relative to the EU budget. Through the change Poland willgain, whereas some large net contributors will lose, i.e. the Netherlands, Sweden andthe United Kingdom.